Promiscuity, inbreeding and dispersal propensity in great tits - Szulkin, M; Chapman, JR; Patrick, S; Sheldon, B (2012)
Mating with relatives leads to inbred offspring, which are likely to experience reduced fitness owing to the expression of deleterious recessive alleles. Constraints in social mate choice do not always allow individuals to avoid pairing with kin. A possible means of inbreeding avoidance is to engage in extrapair copulations with unrelated extrapair individuals. In a population of great tits, Parus major, we tested whether broods of related partners were characterized by higher rates of extrapair paternity than neighbouring outbred broods. Contrary to our expectations, broods sired by related partners had about 60% lower rates of extrapair paternity relative to outbred broods. Parental status of female birds categorized as inbreeding, outbreeding locally born or outbreeding immigrant explained 29% of the variance in the proportion of extrapair young in their broods. Outbreeding locally born females and inbreeding females did not differ in rates of extrapair paternity, but had significantly fewer extrapair young than outbreeding immigrant females. Thus, the contrasting differences in the proportion of extrapair young in inbred and outbred great tit broods do not appear to be the consequence of inbreeding per se. Instead, variation in both promiscuity and inbreeding may reflect the operation of broad-scale effects caused by variation in large-scale dispersal behaviour. © 2012 The Association for the Study of Animal Behaviour.